(untitled) (Eurasian Journal of Engineering and Technology, 2023)
The proposed article deals with the problems of developing the information and computer culture of students in the framework of informatization of education. The author reveals the importance of introducing innovative information technologies into the educational process in order to create a unified information environment in the educational space of an educational institution. The actualization of the problem under study is connected with the possibility of using information technologies to intensify all levels of the educational process, improve its efficiency and quality. The article analyzes the possibilities of using a computer to move an individual to a qualitatively new stage of his development. In the context of informatization of society, the significance of the formation of information and computer culture of students is revealed. The article shows what functions of computer culture structure the value, cognitive and behavioral components. In this regard, it is concluded that it is the development of information and computer culture that is the most important condition for providing opportunities for the individual to become a full member of the modern information society.